2021
DOI: 10.1111/srt.13084
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Fibres in the subcutaneous tissue: Is there a difference between superficial and muscular fascia? A cadaver study

Abstract: Background In last years the role of fascia in proprioception and pain has been confirmed in numerous papers, but the real structure of fasciae is not still entirely known. To date, many studies have evaluated the elastic fibres in arteries, ligaments, lungs, epidermis and dermis, but only two studies exist about the elastic fibres in the fasciae, and they did not distinguish between superficial (in the subcutaneous tissue) and deep/muscular fasciae. The aim of the study was to assess the percentage of elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…The morphological features of the retinacula in the wrist and in the ankle studied showed similar features with the deep fascia, which tended to decrease in thickness, which was most evident in the iliotibial tract and extensor retinaculum of the ankle (Table 1). Moreover, in all-full thickness at 36th week of development, a precise organization of the deep fascia was seen, similar to those described in adults [18,19], while the samples collected around the joints did not present the thickening typical of the fascial reinforcements/retinacula, and only in those of the lower limb started to appear the organization in sublayers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The morphological features of the retinacula in the wrist and in the ankle studied showed similar features with the deep fascia, which tended to decrease in thickness, which was most evident in the iliotibial tract and extensor retinaculum of the ankle (Table 1). Moreover, in all-full thickness at 36th week of development, a precise organization of the deep fascia was seen, similar to those described in adults [18,19], while the samples collected around the joints did not present the thickening typical of the fascial reinforcements/retinacula, and only in those of the lower limb started to appear the organization in sublayers.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, an analysis of our results showed that the quantity of elastic fibers, during gestation, is negligible. As reported by Pirri et al [19], "Elastic component, inside loose connective tissue, allows the fibrous layers to move with respect to the adjacent one and to return to initial", supporting the hypothesis that the movement, the load and the gravity stimulate their development in the deep fascia mixing their elastic capacity and of force transmission (Appendix A).…”
Section: Discussionsupporting
confidence: 72%
“…These findings indicate that the superficial fascia in the arm and in forearm tends to be thicker posteriorly, indicating a greater role in organizing the subcutaneous tissue in these compartments [ 20 ]. Indeed, the superficial fascia, being a fibrous-elastic connective tissue with fat mingled, was observed to be double in the posterior region at different levels of arm, holding the subcutaneous tissue together and allowing it to maintain its integrity in the transfer of forces during the movement [ 22 ]. Moreover, the superficial fascia splits around major subcutaneous vessels and nerves [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Superficial Fascia (SF, 700 μm thickness, Pirri et al, 2022 ) was collected in the abdominal region (from three volunteer patients who were undergoing abdominoplasty at the Plastic and Reconstructive Surgery Unit of the University of Padua), and in the hip area (from six volunteer patients undergoing elective surgical procedures at the Orthopaedic Clinic of the University of Padua).…”
Section: Methodsmentioning
confidence: 99%